Dbal phur nag po sgrub paʼi las tshogs skor; Bonpo liturgical texts focussing upon the worship of Vajrakila, recovered from their place of concealment at Spa-gro Phug-gcal in Bhutan by Khu-tsha Zla-ʼod - Khu-tsha Zla-ʼod, b. 1024 (distributor Tibetan Bonpo Monastic Centre, Dolanji, H.P., 1974)
Esoteric rituals of the Bonpo tradition of Lamaism.